Table of Content - - (Journal of Islamic Sciences, 2023)
Table of Content:1. The meanings of Imperative Structures in the Rules of FundamentalismDr. Amani Ali Esmail2. Underage marriage between destination and outcomesDr. Muneef Sharyan Ahmed Al-Falahi3. Chapter (what came about the mention of seal of the messenger of God, my God's prayers and peace be upon him, from the book (Explanation of Shamail al-Nabawi) by Imam Lari – Study and InvestigationDr. Ameera Ahmed Mohsen Otaifah4. The Brief of Al-Tahtheeb in the Interpretation, by Imam Al-Mu’ayyad Bellah, Surat Al-Nisa from verse (174) to the end of it – Study and Investigation –Mr. Farouq Ali Yahya Othman Abbass5. The Chapter of the “Marriage of Polytheists” in the Book of Al-Omdah Lil Omah Fi Mathahib Al-Aemah Fi Al-Mabahib Al-Fikhia Wal Asrar Al-Shariyah by Imam Yahya bin Hamza Al-HosainiMr. Abduljalil Abdullah Ahmed Hazbar6. The Privileges of Men over Women in Family Matters: A Comparative Jurisprudential StudyMrs. Asma'a Mohammed Ali7. Study of the book Hashiyat Al-Imam Ibn Bilal Al-Hanafi (d. 957 AH) on the explanation of Mukhtasar Al-Muntaha for Al-UdudDr. Reem Ahmed ALthobaiti8. The reasoning of the judicial ruling in administrative cases and its applications in the courts of the Kingdom of Saudi Arabia (An applied systematic study)Mr. Anas Ayed Al-Juma
Keywords: Journal of Islamic Sciences